Land, climate, energy, agriculture and development in the Sahel: Synthesis paper of case studies under the Sudano-Sahelian initiative for regional development, jobs, and food security - Alisher Mirzabaev; Tekalign Gutu Sakketa; Mouhamadou Bamba Sylla; Kangbéni Dimobe; Safietou Sanfo; Assefa Admassie; Degnet Abebaw; Ousmane Nafolo Coulibaly; Adamou Rabani; Boubacar Ibrahim; Abdou Latif Bonkaney; Abdoul Aziz Seyni; et al. (University of Bonn, Center for Development Research (ZEF), 2021)
This paper synthesizes a set of national case studies conducted in the Sahelian countries during 2019- 2020 as a collaboration between national universities and research institutes, and the Center for Development Research (ZEF), University of Bonn, with contributions from the Agrhymet Regional Centre, Permanent Interstate Committee for Drought Control in the Sahel (CILSS). These case studies provide up-to-date knowledge and critical insights on the nexus of land degradation, climate change and energy in the Sahel. The current synthesis paper highlights their major findings and provides crosscutting and cross-regional analytical conclusions. First, the synthesis paper explores current trends in the Sahel region on land use and land degradation, energy use and supply, climate change projections and impacts, as well as their interactions and links to agricultural growth, food security, poverty reduction, and peace in the region. Second, technological, socio-economic and policy solutions at the nexus of land, water, energy and climate challenges that enable environmentally sustainable and socially inclusive rural development in the Sahel are discussed, including their interactions and implications for peace and stability in the region. The findings show that such socio-economic solutions as improving access to markets, strengthening social safety nets, increasing investments to transport and energy infrastructures, promoting land tenure security, expanding off-farm employment opportunities can greatly contribute to rural development in the Sahel, particularly by aiding climate change resilience and sustainable land management. Key technological innovations highlighted across the case studies include expanding irrigation and adopting water use efficient irrigation techniques, crop diversification, expanding agricultural mechanization, investing into restoring and rehabilitating degraded lands through reforestation, afforestation and agroforestry practices. The key lessons learnt from ongoing national policy initiatives for sustainable development highlight the importance of active stakeholder consultation and participation in policy formulation, institution of effective policy monitoring and assessment mechanisms, and avoiding of excessive reliance on external sources of funding for the successful implementation of sustainable development policies and programs. Based on these findings, the synthesis paper proposes an agenda for applied research to provide guidance to and accompany promising development strategies in and for the region.
Keywords: O1; O2; O3; Q1; Q2; Q4; Q5; J43; 330; Sahel; water-energy-food security nexus; food insecurity; land degradation; climate change adaptation; development policies; job creation; infrastructure; conflicts; future research agenda